AdvancED Flex Application Development Building Rich Media X - Blank, R.; Otuome, Hasan; Gonzalez, Omar.; Charlton, Chris; SpringerLink (Online service) (Berkeley, CA : Apress, 2008)
Many Flex books cover the basics$1 (Bthis book does something different, and goes far further. The authors, leading Flash platform developers at Almer/Blank, working with Adobe User Group communities, are the creators of the Rich Media Exchange (RMX), a social media network for Adobe developers. In covering just how the RMX was built, this book contains all the knowledge you need to build similar large-scale rich Internet applications with Adobe Flex. From the inception of the idea through to deployment, the authors show the techniques needed to plan and build advanced applications. You'll learn how to use forms, styles, validators, video, sound analysis, and framework caching, ensuring you make the most of the features introduced in Flex 3. Powerful applications require solid back ends. This book shows how to hook up a Flex application to PHP back-end systems such as Drupal and OpenAds. You'll learn how various parts of the RMX were built, including the blogs, event calendar, jobs board, and advertising system$1 (Belements that come together to really showcase the power of Flex. The RMX is built by Adobe developers for Adobe developers$1 (Ba rewarding community relationship that guarantees results. The same spirit is carried into this book, with the authors wanting and helping to take you to the next level of Flash application development.s
Planning the RMX -- to Flex 2 Applications -- Defining the Application: introducing the RMX -- Planning the Application: Building the RMX -- Building the RMX Core Functions -- Preparing to Get to Work -- Styling Flex -- Collecting and Working with Aggregated Content -- Secondary Navigation -- Forms and Validation -- User Communications -- Working with Video -- Advertising and Flex -- Building out New Features -- Building the Blog -- Building the Jobs Board -- Building the Event Calendar -- Ideas for the Future: Extending the RMX -- Special Topics -- RSLs and Persistent Framework Caching -- Search Engine Optimization for Flex -- Building an Audio Visualizer in Flex.
Keywords: Computer science; Software engineering; Computer Science; Software Engineering/Programming and Operating Systems; Electronic books